Conceptual design of kenaf fibre-reinforced thermoplastic composites using concurrent engineering method for the side-door impact beam - Shaharuzaman, Mohd Adrinata (2020)
This thesis details the conceptual design of kenaf fibre reinforced thermoplastic composite for a side-door impact beam in the context of the product development process. The overall process was implemented using the concurrent engineering approach, encompassing the defining weight of criteria for the product design specification, natural fibre materials selection, thermoplastics matrix materials selection, design concept generation, and the design concept selection. Seven criteria of the product design specification were considered in this thesis based on the literature on the side-door impact beam and natural fibre reinforced polymer composites of automotive components. Six criteria were then computed using the Analytic Hierarchy Process (AHP) method to determine their weight of criteria and was applied throughout this thesis. The results show that the performance, PF, has the highest weightage with an average value of 0.3566, followed by product cost, PC (0.1971), weight, WG (0.1690), environment, EV (0.1127), disposal, DP (0.0857), and lastly size, SZ (0.0789). The weight of criteria was then recalculated for each process of selection, which depends on the criteria and sub-criteria involved. The materials selection process for natural fibre using the VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method confirmed that kenaf fibre was the most suitable for reinforcement in polymer composites due to its lowest VIKOR value, Q, of 0.0. The VIKOR method was then used to select the suitable thermoplastic matrix material for the polymer composite, and the results showed that the three suitable thermoplastic materials are the polypropylene (PP), low-density polyethylene (LDPE), and high-density polyethylene (HDPE) with Qs of 0.0, 0.0194, and 0.1504, respectively. The concept design development was then performed using the integrated method of Theory of Inventive Problem Solving (Function Oriented Search) (TRIZ (FOS)) – Biomimetics method, which was used to generate the design concepts, then the VIKOR method for the design concept selection. From the TRIZ (FOS) – Biomimetic method, eight design concepts were proposed, and concept design 6 (B-03) was selected as the best design concept for the kenaf fibre reinforced thermoplastic composites of the automotive side-door impact beam based on the analysis made by the VIKOR method, with a value of 0.0156. In conclusion, the conceptual design process for natural fibre reinforced thermoplastic composites of a side-door impact beam using concurrent engineering method shows that the integrated method practises of a systematic approach and structured analysis in the product development process not only minimises time and energy, it is also cost-effective to the designers and engineers making the decisions. This study is limited to the conceptual design stage in the product development process, and it is expected that the methods detailed in this research can provide additional information to the practitioners and be a useful contribution to the automotive product development industry.